Current unmet needs of cancer survivors: Analysis of open‐ended responses to the American Cancer Society Study of Cancer Survivors II. Issue 4 (12th January 2015) - Burg, Mary Ann; Adorno, Gail; Lopez, Ellen D. S.; Loerzel, Victoria; Stein, Kevin; Wallace, Cara; Sharma, Dinghy Kristine B.
<x xml:space="preserve">Abstract</x> BACKGROUND Cancer survivors may continue to experience psychosocial and physical needs related to their cancer experience for many years after treatment. The specification of these needs across cancer types and by survivor characteristics may lead to better prevention approaches and clinical responses. Mixed methods were used to examine responses to an open‐ended question about current unmet needs from a survey of 2‐, 5‐, and 10‐year cancer survivors. METHODS Qualitative techniques were used to code themes of unmet needs from open‐ended responses. These themes were then examined with quantitative techniques to describe the frequency of unmet needs across disease subgroups and demographic subgroups of survivors. RESULTS There were 1514 responses to the open‐ended question on unmet needs. Respondents ranged in age from 24 to 97 years and included proportionately more women, and 18% were minorities (black and Hispanic). Sixteen themes of unmet needs were identified. The number and type of unmet needs were not associated with the time since cancer treatment. Breast cancer survivors identified more unmet needs than other survivors. Male survivors and especially prostate cancer survivors identified personal control problems as current needs. Older cancer survivors identified fewer unmet needs on average than younger survivors. CONCLUSIONS This analysis of an open‐ended question on unmet needs extends our understanding of how cancer survivors perceive problems related to cancer. How cancer‐related needs change over time and differ by sex, race, and ethnicity and how problems with personal control become manifest are areas of inquiry requiring further research. Cancer 2015;121:623–630. © 2015 American Cancer Society.